Defective retrovirus-like 30S RNA species of rat and mouse cells are infectious if packaged by type C helper virus. - Scolnick, E M (1979)
RNA species with properties of defective retrovirus-like 30S RNA genomes have previously been detected in both rats and mice and in some rat and mouse retroviruses. Using cell lines which express high levels of this retrovirus-like RNA, we formed pseudotypes of the 30S RNAs with helper-independent type C viruses. A pseudotype virus complex containing a mouse 30S subunit was transmitted to rat cells, and a pseudotype virus complex containing a rat 30S subunit was transmitted to bat cells. In other transmission experiments, a rat 30S subunit was isolated in nonproducer bat cells without detectable expression of the helper-independent type C virus used to pseudotype it. The results provide further support for the retrovirus-like nature of the rat 30S subunit and provide evidence which supports the protovirus hypothesis proposed by Temin.